Vena Varikosa - Putri Septiani; Heru Sulastomo (The Indonesian Heart Association, 2014)
Varicose vein is a common problem in vein. It is a dilated, elongated, and tortuous vein. It used to be a cosmetic problem, but nowadays it has become a more serious problem, since it can affect quality of life. It usually occurs in the inferior extremities. The venous system is divided into superficial vein, deep vein, perforator vein, and intramuscular sinus venosus. Pathological conditions that usually occur in the vein system are obstruction and valve incompetence. The risk factors of varicose vein are: elderly, history of family with varicose vein, pregnancy, occupation that requires long standing, sedentary life style, and obesity. Ultrasonography (USG) duplex is the most recommended modality to diagnose varicose vein. The classification of this disease is based on chronic venous disease classification, the CEAP (Clinical, Etiology, Anatomy, Pathophysiology) classification. The management for varicose vein includes intervention (sclerotherapy, endovenous ablation, and surgery) and non-intervention (education, compression stocking, and pharmacology) therapy.